1993
DOI: 10.1007/bf00746072
|View full text |Cite
|
Sign up to set email alerts
|

Cell-matrix interactions in cultured dermal fibroblasts from patients with an inherited connective-tissue disorder

Abstract: Indirect-immunofluorescence studies were performed on cultured dermal fibroblasts from patients with Pseudoxanthoma Elasticum (PXE), an inherited connective-tissue disorder the pathogenesis of which is still unknown. Apparent abnormalities of cytoskeletal structures were revealed by using phalloidin and specific antibodies to alfa-smooth muscle actin and to vimentin. Altered expression of integrin receptors for different extracellular matrix components seems to be present in the pathological cells as prelimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…In agreement with biochemical ¢ndings, the immunohistochemical analysis showed alterations a¡ecting PG content and distribution in PXE-a¡ected cell layers [11,14]. Furthermore, preliminary studies from our laboratory showed abnormal cytoskeletal organization in PXE ¢broblasts which might be suggestive for altered cell-matrix interactions [15].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In agreement with biochemical ¢ndings, the immunohistochemical analysis showed alterations a¡ecting PG content and distribution in PXE-a¡ected cell layers [11,14]. Furthermore, preliminary studies from our laboratory showed abnormal cytoskeletal organization in PXE ¢broblasts which might be suggestive for altered cell-matrix interactions [15].…”
Section: Discussionsupporting
confidence: 85%
“…Actually, PXE ¢broblasts produce families of proteoglycans with higher molecular weights compared to controls [11] and which di¡er from controls also for their sulfation characteristic [14]. Moreover, preliminary results, on in vitro cultured cells, seem to indicate that PXE ¢broblasts are characterized by peculiar cytoskeletal structures, consistent with the hypothesis of altered cell-matrix interactions [15].…”
Section: Pseudoxanthoma Elasticum (Pxe) Is An Inherited Connective Ti...supporting
confidence: 66%
“…In PXE, dermal fibroblasts are characterized by changes in cytoskeletal organization (Baccarani Contri et al, 1993) and in cell-matrix interactions (Quaglino et al, 2000). These differences can influence the mitochondria, and it is well known that the mitochondria can modify their functions, depending also on the local qualitative and quantitative characteristics of the extracellular matrix (i.e., glycosaminoglycans, elastinassociated components, proteolytically degraded peptides) (Tiozzo Costa et al, 1988;Gheduzzi et al, 2005) through an interconnected sensory system involving cell-matrix interactions and cytoskeletal components (de Cavanagh et al, 2009).…”
Section: Resultsmentioning
confidence: 99%